Characterization of hepatitis delta virus strains spreading in Abuja, Nigeria (2019)
Hepatitis delta virus (HDV) is responsible for the most severe form of liver disease in humans. So far, eight genotypes (HDV‐1 to ‐8) have been individualized worldwide. Little is known about HDV strains that spread in Nigeria. HDV genotyping was performed in 15 anti–HDV positive samples from a cohort of 306 hepatitis B virus (HBV)‐infected patients in Abuja (Nigeria). Phylogenetic analyses revealed 90% were HDV‐1, two among them clustering with European/Asian HDV‐1, the remaining one being HDV‐6. It was also found that two members of a couple superinfected with the same HDV strain, were enveloped by two different HBV strains of genotype E.